How relevant is the current design of physical education facilities to the quality required in compulsory secondary education in xxi century? The case of Castilla y León (Spain) - García-Unanue, J.; Gallardo, L.; Gil, J. L.; Felipe, J. L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
Physical education facilities are a key in Physical Education, because they influence and limit the educational process and the work of teachers. This study aims to analyze the current state of physical education facilities of Compulsory Secondary Education centers, based on the active legislation and regulations. An ad hoc questionnaire was created for the research, and has been applied to 56 centers inCastilla y León. The results indicate significant deficiencies in all areas analyzed. There are centers with problems in safety and accessibility of physical education facilities. We conclude that measures must be taken in the design of physical education facilities and to correct the existing deficiencies. Include the obligation to use the NIDE Rules in all these actions would ensure safety and quality facilities witch improve the work of teachers and Physical Education lessons.